2017
DOI: 10.1016/j.ymthe.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant LCMV Vectors Induce Protective Immunity following Homologous and Heterologous Vaccinations

Abstract: Successful vaccination against cancer and infectious diseases relies on the induction of adaptive immune responses that induce high-titer antibodies or potent cytoxic T cell responses. In contrast to humoral vaccines, the amplification of cellular immune responses is often hampered by anti-vector immunity that either pre-exists or develops after repeated homologous vaccination. Replication-defective lymphocytic choriomeningitis virus (LCMV) vectors represent a novel generation of vaccination vectors that induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Moreover, all of the previous studies on Listeria -based therapeutic vaccines utilized only LM as an antigen delivery carrier, and in nearly all reports, the same LM-based vaccine was applied repeatedly; that is homologous prime-boost immunization was performed. One drawback of homologous prime-boost immunization is that may result in anti-vector immunity, leading to early bacterial clearance, loss of gene expression and limitation of amplification of cellular immune responses 15 . To attempt to overcome this anti-vector immunity, we innovatively utilized both attenuated LM and LI strains in which the two virulence genes actA and plcB were knocked out to deliver the fused HPV-16 E6E7 antigen protein.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all of the previous studies on Listeria -based therapeutic vaccines utilized only LM as an antigen delivery carrier, and in nearly all reports, the same LM-based vaccine was applied repeatedly; that is homologous prime-boost immunization was performed. One drawback of homologous prime-boost immunization is that may result in anti-vector immunity, leading to early bacterial clearance, loss of gene expression and limitation of amplification of cellular immune responses 15 . To attempt to overcome this anti-vector immunity, we innovatively utilized both attenuated LM and LI strains in which the two virulence genes actA and plcB were knocked out to deliver the fused HPV-16 E6E7 antigen protein.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that arenaviruses mainly infect important immune cells, such as dendritic cells (DCs) and macrophages, at the early stage of infection, which make them an ideal viral vector for vaccine development as they target these antigen-presenting cells (APCs) that can naturally enhance immune responses against the antigenic proteins ( 125 , 126 ). Several studies have utilized reverse genetics technology to generate recombinant LCMV carrying antigenic proteins of interest ( 127 , 128 ). Emonet and colleagues ( 129 ) developed a three-plasmid reverse genetics system to generate a tri-segmented LCMV.…”
Section: Viral Vectored Influenza Vaccinesmentioning
confidence: 99%
“…Given the challenges associated with identifying CD4 T cell peptides presented following antigen exposure, coupled with the significant resources required to develop and validate a TCR transgenic, most studies have instead leveraged existing tools designed to evaluate the immune response to a model antigen by incorporating the antigen into the overall immunogen studied. This approach has been used for decades to study the immune response to viruses, bacteria, transplanted tissue and transfusion of blood products [ 60 , 65 , 66 , 67 , 68 ]. In each setting, despite the similar nature of the antigen targeted, the observed immune response appears to largely be governed by the vehicle containing the model antigen [ 60 , 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used for decades to study the immune response to viruses, bacteria, transplanted tissue and transfusion of blood products [ 60 , 65 , 66 , 67 , 68 ]. In each setting, despite the similar nature of the antigen targeted, the observed immune response appears to largely be governed by the vehicle containing the model antigen [ 60 , 65 , 66 , 67 , 68 ]. However, while this strategy has been employed in a variety of settings and has provided important insight into immunology in general, similar strategies have not been employed to define the CD4 T cell response to protein-based drug therapies.…”
Section: Introductionmentioning
confidence: 99%